Ultrasonic characterisation of particle retention by a double porosity medium. Issue 9 (16th April 2019) - Bai, Ruonan; Alem, Abdellah; Franklin, Hervé; Tinel, Alain; Wang, Huaqing; Kachkouch, Fatima; Taibi, Said; Bizet, Laurent
ABSTRACT: A study was undertaken to characterise the evolution of the clogging of various porous media during filtration experiments. Long-term tracer tests were carried out at various flow velocities. To highlight the effects of intraporosity on transport and retention mechanisms, both single porosity and double porosity media (DPM) were used. The presence of matrix porosity in the two investigated DPM provided additional sites, promoting retention of suspended particles (SP). The particle size distribution (PSD) of the recovered particles increased with time. However, and due to the additional retention sites in intraporosity, the changes in PSD with time were slower for tests on DPM. Ultrasonic transmission was used to detect modifications to the properties of the porous media induced by particle retention. The results demonstrate the capacity of ultrasound for detecting the evolution of physical clogging as a consequence of particle deposition.